6.9(13+9u)=2

Simple and best practice solution for 6.9(13+9u)=2 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 6.9(13+9u)=2 equation:



6.9(13+9u)=2
We move all terms to the left:
6.9(13+9u)-(2)=0
We add all the numbers together, and all the variables
6.9(9u+13)-2=0
We multiply parentheses
62.1u+89.7-2=0
We add all the numbers together, and all the variables
62.1u+87.7=0
We move all terms containing u to the left, all other terms to the right
62.1u=-87.7
u=-87.7/62.1
u=-1+16/38.8125

See similar equations:

| w=–9+2w | | x/4+52=58 | | I6x+3I=5 | | x/4+52=68 | | 8x-15=56 | | -25=-7=6x | | 3-1=c-1 | | 24-0,06x=0 | | 19−g=7g=15 | | x‐8=‐3 | | 15÷3x=50x= | | z/6-3=2 | | 2x-9=30+23 | | b=68b=48. | | 6x+8-48x-12=6x+10 | | 1728x^2-331.2x-43.88=21425 | | 3x+9=2x+5* | | -4x+6=94 | | 9x-17=-17+9x* | | (-4x+5)+-13x+39)=180 | | -7+5x=5x+9* | | 6x−7=11 | | 27+4x=180 | | X-9=0.5x= | | 2x+180-41=x+41 | | -12/2+x=2 | | b/5-5=-3 | | (w-3)=(w-7) | | 5500=5000+50x-x^2 | | (10+8)8=(2x-34+6)6 | | z+6=‐5 | | 5s–8=22 |

Equations solver categories